ANALISIS TEGANGAN DAN MODULUS ELASTISITAS STRUKTUR KISI YANG DI DESAIN MENGGUNAKAN SCRIPT BERBASIS PYTHON - Eko Pujiyulianto; Muhamad Fatikul Arif; Abdul Muhyi; Fajar Paundra; Ariq Athallah; Daniel Christover Munte (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
This study aims to evaluate TPMS lattice structure designs using Python scripts, which will later be used for lattice shell helmet designs. The structural design evaluation will be performed using numerical methods by varying the volume fraction. The lattice structures to be evaluated include FischerKochS, Honeycomb, pmy, and SchoenFRD. The CAD models of the lattice structures will be generated using Python-based scripts. The volume fraction variations are achieved by altering the shell thickness values in the Python scripts. The analysis will be conducted using numerical methods based on finite element analysis with static analysis and an elastic material model. The material used is ABS. Based on the research results, it indicates that the thickness specified in the script (thickness) cannot be defined as the actual shell thickness. The relationship between thickness and volume fraction indicates that each lattice structure will produce a different volume fraction when the shell thickness is varied. As the shell thickness increases, the volume fraction of the lattice structure also increases. volume fraction in lattice structures does not affect stress in a linear manner. The highest stress is observed in the pmy structure, followed by the Honeycomb and FischerKochS structures, while the SchoenFRD structure exhibits the lowest stress values. The most suitable design for use as a lattice structure in helmets is the ScheonFRD design. This is due to the design capability of ScheonFRD in distributing stress across the structure.